Agroforestry to stabilize soils - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Long-term benefits in terms of erosion control, improved fertility and hydrological characteristics of soil, have been shown in agroforestry trials carried out by scientists at the Central Tuber Crops Research Institute, India. The experiments were...